2013
DOI: 10.1172/jci68458
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of disease activity in muscular dystrophies by noninvasive imaging

Abstract: Muscular dystrophies are a class of disorders that cause progressive muscle wasting. A major hurdle for discovering treatments for the muscular dystrophies is a lack of reliable assays to monitor disease progression in animal models. We have developed a novel mouse model to assess disease activity noninvasively in mice with muscular dystrophies. These mice express an inducible luciferase reporter gene in muscle stem cells. In dystrophic mice, muscle stem cells activate and proliferate in response to muscle deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…They found luciferase activity mainly in the proximal limb muscles as early as 3 months of age, with some involvement in the distal muscles starting at 6 months, and increasing luciferase activity in both proximal and distal muscle groups up to 18 months of age. Further examination of these mice showed a correlation between intensity of luciferase signal (as determined by bioluminescent imaging), number of luciferase positive fibers (as determined by immunohistochemistry), and extent of histopathology, including centrally nucleated fibers and fibers that express embryonic myosin heavy chain, a marker for newly regenerated myofibers (5). This validates luciferase imaging as an alternative to conventional measures of disease progression in muscular dystrophy.…”
Section: Future Applicationssupporting
confidence: 58%
See 2 more Smart Citations
“…They found luciferase activity mainly in the proximal limb muscles as early as 3 months of age, with some involvement in the distal muscles starting at 6 months, and increasing luciferase activity in both proximal and distal muscle groups up to 18 months of age. Further examination of these mice showed a correlation between intensity of luciferase signal (as determined by bioluminescent imaging), number of luciferase positive fibers (as determined by immunohistochemistry), and extent of histopathology, including centrally nucleated fibers and fibers that express embryonic myosin heavy chain, a marker for newly regenerated myofibers (5). This validates luciferase imaging as an alternative to conventional measures of disease progression in muscular dystrophy.…”
Section: Future Applicationssupporting
confidence: 58%
“…They first injured the TA muscles with cardiotoxin and compared the luciferase signal between the injured and uninjured limbs. Luciferase activity increased following injury, and immunohistochemical studies confirmed that luciferase-expressing cells were present in the injured TA as nascent myofibers and myotubes (5). This suggests that the noninvasive measurement of luciferase activity in the Pax7Cre ER /LuSEAP strain is an accurate measure of the proliferative activity of satellite cells and therefore has potential to be used to measure muscle regeneration in muscular dystrophy models as well.…”
Section: A "Regeneration Reporter" Mouse Strainmentioning
confidence: 80%
See 1 more Smart Citation
“…Luciferase-based imaging has been widely used in mice for monitoring gene expression, cell proliferation and migration, and bacterial and viral infections (Contag and Bachmann, 2002;Luker and Luker, 2008;Liu et al, 2011;Tinkum et al, 2011;Martínez-Corral et al, 2012;Maguire et al, 2013). Detection of bioluminescent signals generated from the luciferase-luciferin reaction is sensitive, virtually free of background noise, and can reveal biological information even from deep tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Maguire and colleagues monitored luciferase activity in mice expressing an inducible luciferase reporter gene in muscle stem cells. These stem cells proliferated in response to muscle degeneration, thus increasing the level of luciferase expression in dystrophic muscle [131]. …”
Section: Cell Labelingmentioning
confidence: 99%